1987
DOI: 10.1037/0021-9010.72.2.294
|View full text |Cite
|
Sign up to set email alerts
|

The social psychology of eyewitness accuracy: Misleading questions and communicator expertise.

Abstract: The authors are grateful to Robert Maura for his help in various phases of this research, and to R. Edward Geiselman for providing the crime clip used in Experiment 2. We would also like to thank Pamela Burke, Craig Smith, and Anthony Ahrens for their helpful comments on an earlier version of this article, and Andrew Blaine, Gary Rothschild, Kazu Sano, and Michael Tuchin for serving as confederates in these experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
113
3

Year Published

1989
1989
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(120 citation statements)
references
References 13 publications
4
113
3
Order By: Relevance
“…In particular, the conditions under which witnesses encounter misinformation can have a profound impact on their suggestibility. Along these lines, prior research has shown that people are far less susceptible to misinformation delivered by a peer than by an authority figure (Ceci, Ross, & Toglia, 1987;Dodd & Bradshaw, 1980;Lampinen & Smith, 1995;Smith & Ellsworth, 1987;Underwood & Pezdek, 1998), and that repeatedly encountering misinformation can increase its likelihood of being reported later (Foster, Huthwaite, Yesberg, Garry, & Loftus, 2012;. As indicated in the Introduction, some research has also shown that encountering misinformation from a narrative or a question can influence its effectiveness at altering memory reports, but the results are somewhat mixed.…”
Section: Discussionmentioning
confidence: 85%
“…In particular, the conditions under which witnesses encounter misinformation can have a profound impact on their suggestibility. Along these lines, prior research has shown that people are far less susceptible to misinformation delivered by a peer than by an authority figure (Ceci, Ross, & Toglia, 1987;Dodd & Bradshaw, 1980;Lampinen & Smith, 1995;Smith & Ellsworth, 1987;Underwood & Pezdek, 1998), and that repeatedly encountering misinformation can increase its likelihood of being reported later (Foster, Huthwaite, Yesberg, Garry, & Loftus, 2012;. As indicated in the Introduction, some research has also shown that encountering misinformation from a narrative or a question can influence its effectiveness at altering memory reports, but the results are somewhat mixed.…”
Section: Discussionmentioning
confidence: 85%
“…One of the possible social mechanisms contributing to these effects is the tacit expectation that what the questioner is saying is true (Vosniadou, 1982), a mechanism that can also be derived from the Grician maxim of quality (Grice, 1975). As Smith and Ellsworth (1987) have shown, the degree to which the questioner is regarded as an expert affects the influence of misleading questions. However, as Schwarz (1994) has noted, research on misleading questions has been limited to situations in which the questioner was assumed to be a cooperative communicator.…”
Section: Studymentioning
confidence: 99%
“…This strategy can serve a number of purposes, from questioning the witness's credibility to disorienting him or her. The introduction of such information after an event has been shown to modify the original recollection of the event (e.g., Christiaansen, Sweeny, & Ochalek, 1983;Read & Bruce, 1984;Smith & Ellsworth, 1987;Weinberg, Wadsworth, & Baron, 1983;Yuille, 1980). Either of the two framing strategies can be introduced by the modification of simple grammatical and semantic elements in the structure of the question.…”
Section: Studymentioning
confidence: 99%
“…Susceptibility to misinformation in the eyewitness context has been found to depend on the perceived credibility of the source of misinformation. For example, Smith and Ellsworth (1987) found that if the source of erroneous postevent information is thought to be competent and knowledgeable, this person's erroneous information is believed, and memory accuracy is compromised (see also Kwong See, Hoffman, & Wood, in press). Similarly, Dodd and Bradshaw (1980) found that if subjects were led to believe the source was not honest because the source had an intention to mislead, erroneous information provided by this source did not influence memory reports.…”
mentioning
confidence: 99%